Masking Ability of Two Super High Translucent Zirconia Ceramics Compared with Lithium Disilicate Reinforced Glass Ceramic - Mahnaz Hatami; Abbas Fallah Tafti; نوروزی norouzi; Alireza Danesh Kazemi (Mashhad University of Medical Sciences, 2022)
Introduction: The masking ability of dental ceramics has an important role in the final color of all-ceramic restorations. The masking ability of super-high translucent zirconia is not clearly determined. This study aimed to evaluate the masking ability of two super high translucent zirconia (Zolid fx and DD cubeX2) in comparison to lithium disilicate reinforced glass ceramic (IPS e.max CAD LT).Materials and Methods: In this experimental study, 30 ceramic discs with 1 mm thickness and 10 mm diameter in two groups of super-high translucent zirconia (Zolid fx and DD cubex2) and one group of lithium disilicate reinforced glass ceramic (IPS e.max CAD LT) were fabricated (n=10). To determine the masking ability value (ΔE), a spectrophotometer was used to measure the color parameters of each sample (L*, a *, b*) in black and white backgrounds. One-way ANOVA and Tukey Post Hoc statistical tests were used to analyze the data. The level of significance was considered at 0.05.Results: The mean of ΔE in the three groups of IPS e.max CAD LT, Zolid fx, and DD Cubex2 were 8.37±0.47, 9.87±0.25, and 9.11±0.78 respectively. Significant differences were found in the ΔE values in the three groups (P<0.001).Conclusion: The masking abilities of two super high translucent zirconia Zolid fx and DD CubeX2 were lower than IPS e.max CAD LT. This ability was lower in Zolid fx than in DD cubeX2.